UJI AKTIVITAS ENZIM SELULASE ISOLAT BAKTERI DARI SEDIMEN LAMUN PERAIRAN RENDANI MANOKWARI - Tirza Bandi; Hermawaty Abubakar; Rina A Mogea (Jurusan Biologi, FMIPA, Universitas Papua, 2018)
ABSTRACTIndonesia has the potential of renewable natural resource which are abundant both in number and types of plants containing cellulose fiber. In natures cellulose cannot be completely degraded because it needs of microorganisms such as fungi and bacteria which will produce cellulase enzymes so that it can degrade cellulose in nature. The purpose of this study was to analysed the activity of cellulase enzymes produced by bacterial isolates obtained from seagrass sediments. Cellulase activity of 11 bacterial isolates was determined by the cellulotic index value passing through the Congo Red staining method on 1% CMC solid media. A total of seven isolates indicated a positive result and the highest index value was produced by SI-E isolates, that is 4.7 mm. After that the value of cellulase enzyme activity from the seven positive isolates was determined by counting substrate reducing sugars through the 3.5-dinitrosalicylic (DNS) method. The results showed that SI-H isolates had the highest activity of 0.071 U/mL. ABSTRAKIndonesia memiliki potensi berupa sumber daya alam terbaharukan yang melimpah baik dalam jumlah maupun jenis tumbuhan yang mengandung serat selulosa. Di alam selulosa tidak dapat terdegradasi secara sempurna oleh karena itu dibutuhkan bantuan mikroorganime seperti jamur dan bakteri yang akan menghasilkan enzim selulase sehingga dapat mendegradasi selulosa yang berada di alam. Tujuan dari penelitian ini adalah untuk menganalisis aktivitas enzim selulase yang dihasilkan oleh isolat bakteri yang digunakan. Aktivitas selulase dari 11 isolat bakteri ditentukan dengan nilai indeks selulotik melaluli metode pewarnaan merah kongo pada media padat CMC 1%. Sebanyak tujuh isolat yang menandakan hasil positif dan nilai indeks tertinggi dihasilkan oleh isolat SI-E yaitu 4.7 mm. Setelah itu nilai aktivitas enzim selulase dari ketujuh isolat positif ditentukan dengan menghitung gula pereduksi substrat melalui metode 3.5-dinitrosalisilat (DNS). Hasil menunjukkan isolat SI-H memiliki aktivitas tertinggi yaitu 0.071 U/mL.